Employing popular children's literature to teach elementary school chemistry: an engaging outreach program - Wally, Laura M., author; Levinger, Nancy E., author; Grainger, David W., author (Colorado State University. Libraries, 2004)
Popular cultural themes or fads can provide an effective vehicle to enthuse students about science. The program described here uses current children's literature in a versatile chemical education activity. This activity generates excitement in elementary school students because of the integration of the popular Harry Potter literature series with hands-on experiments. Elementary school student participants are prompted to explore three main scientific topics during this activity: properties of solids, liquids, and gases ; ethics in science ; and the scientific method. Undergraduate and high school student volunteer mentors are readily trained to conduct the activity within elementary schools via an introduction to the philosophy of the exercise in conjunction with working through the activity themselves. As an outreach activity it serves to connect undergraduate and high school students both with faculty and their community.
Keywords: Chemistry -- Study and teaching (Elementary) -- Activity programs; Children's literature, English; Potter, Harry (Fictitious character)